1995
DOI: 10.1288/00005537-199505000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Meningoencephalic herniation into the middle ear: A report of 27 cases

Abstract: Meningoencephalic herniation into the middle ear is a rare and potentially life-threatening condition that may require prompt surgical intervention. Preoperative diagnosis is based on a high index of suspicion. Sometimes, however, meningoencephalic herniation is discovered during surgery. High-resolution computed tomography and magnetic resonance imaging should be performed to confirm the diagnosis and to evaluate the extension of the herniated tissue. This article discusses the diagnostic approach, management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
67
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 19 publications
2
67
0
1
Order By: Relevance
“…This occurrence is, in fact, very well known by neurootologists and skull base surgeons who are familiar with the surgical anatomy of the middle cranial fossa. 16 Multiple areas of bone dehiscence of the tegmen tympani and petromastoid region have been found in up to 34% of dissected temporal bones in postmortem anatomical studies, with bilateral deficits described in 20% of the specimens examined by Kapur et al 1,22 Idiopathic meningoencephaloceles of the middle ear occur most frequently around the seventh decade of life, 4 and Moreano and associates 32 in an anatomical study involving 1000 human temporal bones observed an inverse relationship between thinning of the temporal bone around the carotid artery and age of the dissected anatomical specimen. A thin bone covering was observed in 17.3% of temporal bones in specimens 40 years old or older, whereas such thinning was present in only 8.3% of younger specimens.…”
mentioning
confidence: 99%
“…This occurrence is, in fact, very well known by neurootologists and skull base surgeons who are familiar with the surgical anatomy of the middle cranial fossa. 16 Multiple areas of bone dehiscence of the tegmen tympani and petromastoid region have been found in up to 34% of dissected temporal bones in postmortem anatomical studies, with bilateral deficits described in 20% of the specimens examined by Kapur et al 1,22 Idiopathic meningoencephaloceles of the middle ear occur most frequently around the seventh decade of life, 4 and Moreano and associates 32 in an anatomical study involving 1000 human temporal bones observed an inverse relationship between thinning of the temporal bone around the carotid artery and age of the dissected anatomical specimen. A thin bone covering was observed in 17.3% of temporal bones in specimens 40 years old or older, whereas such thinning was present in only 8.3% of younger specimens.…”
mentioning
confidence: 99%
“…In the study by Spiros Manolidis, the predisposing factors for dural herniation include: prior ear surgery such as mastoidectomy (radical or modified radical), meningitis, cholesteatoma and active chronic otitis media [2,4]. Iatrogenic injuries incurred during radical and modified radical mastoidectomy account for more than 59 to 77 % of the causes of encephalocoele [2,5]. Dural defect can be due to various causes such as spontaneous-congenital and idiopathic [6], traumatic [7], iatrogenic and inflammatory [8].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is based on a high index of suspicion and clinical evaluation. High resolution computed tomography and Magnetic resonance imaging (MRI) could be used as preoperative evaluation modalities to confirm the diagnosis and assess the extent of lesion [5]. Brain herniation into a post-mastoidectomy cavity is rare and can be radiologically confused with cholesteatoma on the high resolution CT scan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fascia (temporalis or fascia lata) muscles, cartilage, bone, perichondrium, proplast, fi brin glue have all been used either simply or in combination [1]. Herniated brain tissue that is strangulated is nonfunctional and can be safely resected with no residual dysfunction [9,14]. Kuchweide R et al (1999) have described the surgical management of encephalocoele by a 5-layer closure using a transmastoid approach with minicraniotomy.…”
Section: Discussionmentioning
confidence: 99%